Emerging infectious diseases : using PCV2 as a model of disease transmission dynamics at the livestock-wildlife interface in Uganda - Jonsson, L. (Swedish University of Agricultural Sciences, 2013)
Uganda is considered a “hotspot” for emerging infectious diseases (EIDs), meaning that it is a high-risk country for new infectious diseases to originate. The pig production is increasing drastically in Uganda and many of the pigs are free ranging and can come in contact with wildlife. Porcine circovirus 2 (PCV2) is a ubiquitous virus and causal agent of porcine multisystemic wasting syndrome (PMWS). Not only is PCV2 found in domestic pigs all around the world but it has also been shown to infect wild boar. PCV2 is, in this study, used as a model for disease transmission dynamics because it is spread among pigs throughout the world, has some genetic variation and has been found in both domestic and wild pigs.The aims of this study were to investigate the disease transmission dynamics in the livestock- wildlife interface in Uganda with PCV2 as a model, as a part of the EID surveillance, and to estimate the prevalence of PCV2 in domestic pigs in Uganda.Ninety-one domestic pigs around Murchison Falls national park were sampled and analyzed with SybrGreen RT-PCR for three different PCV2 genogroups, SG1, SG2 and SG3. Attempts to catch warthogs were made but unfortunately without success. Consequently no conclusions regarding disease transmission between wild and domestic pigs could be made. The domestic pig samples were all negative for SG1 and SG2 but for SG3 a point prevalence of 77% was found. SG3 is also known as PCV2b and is the most common PCV2 type in most other countries as well. PCV2b is also the genogroup most associated with PMWS.For future projects both Uganda and suids could be important areas of study both for increasing the understanding of disease transmission dynamics in the livestock-wildlife interface and also for EID surveillance.